Effect of Mn-content of ER5356 welding rods on mechanical properties of Al-alloys joints - Ni, Xianpeng; Xu, Shaohua; Mu, Hua (Frontiers in Mechanical Engineering, 2024)
Introduction: Compared with imported welding wire, domestic aluminum alloy welding wire has more internal inclusion defects. To improve the welding quality and reliability of aluminum alloy, the welding performance of aluminum alloy was improved by adding different content of Mn element. Methods: ER5356 aluminum alloy ingot with different Mn content (0.05% and 0.15%) was prepared by semi-continuous casting and gravity casting. After stretching, the mechanical properties and microstructure of ER5356 aluminum alloy were studied. In addition, the microstructure, microhardness and mechanical behavior of ER5356 aluminum alloy welding wire with 6082 and 7005 aluminum alloy joints were studied. Results and Discussion: Compared with gravity casting, the yield strength and tensile strength of ER5356 (0.15% Mn) were increased by 12.8% and 3.17% respectively. The head influence zone of the joint made of metal wire containing 0.15% Mn is slightly wider than that of the joint made of ER535 (0.05% Mn) containing 0.05% Mn. The quality of ER5356 aluminum alloy welding wire blocked by semi-continuous casting is better than that of ER5356 aluminum alloy welding wire blocked by gravity casting method. Mn element can improve the metal deposition process in welding. Conclusion: The research method can improve the welding current control and welding quality, and has important practical significance in improving the mechanical properties of welding seams.